PENDAMPINGAN PENDESAINAN PERANGKAT PEMBELAJARAN BERBASIS PMRI BAGI GURU KABUPATEN MUSI RAWAS UNTUK MENINGKATKAN PRESTASI PESERTA DIDIK - Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Somakim, Somakim; Kurniadi, Elika; Sukmaningthias, Novika; Simarmata, Ruth Helen (UNIVERSITAS PGRI MADIUN, 2022)
Abstract. In preparing the learning process in the classroom, teachers must prepare learning tools. Learning tools consist of a syllabus, lesson plans, student worksheets, and assessments in the form of tests and non-tests. This service activity aims to provide training and the application of research related to the development of learning tools for middle school mathematics MGMP teachers, and to find out the response of high school Mathematics MGMP teachers to the assistance in developing learning tools provided. This community service implementation model is a mentoring model to improve teacher professionalism in preparing teaching and learning activities, especially in preparing learning tools, the need for basic understanding of theory, and its application. The number of participants who attended this activity was 33 mathematics teachers from Musi Rawas district. Overall, the implementation of this service activity went smoothly without any significant obstacles, only some participants were left from the Zoom meeting when the activity was carried out in sync due to signal interference. The results of the satisfaction response questionnaire analysis get positive results Abstrak. Dalam mempersiapkan proses pembelajaran di kelas, para guru harus menyiapkan perangkat pembelajaran. Perangkat pembelajaran terdiri dari silabus, rencana pelaksanaan pembelajaran, lembar kerja peserta didik, serta lembar penilaian baik berupa tes maupun non tes. Kegiatan pengabdian ini bertujuan untuk memberikan pelatihan dan penerapan penelitian yang berkaitan dengan pengembangan perangkat pembelajaran bagi guru – guru MGMP matematika sekolah menengah, dan mengetahui respon guru -guru MGMP Matematika sekolah menengah terhadap pendampingan pengembangan perangkat pembelajaran yang diberikan. Model pelaksanaan kegiatan pengabdian kepada masyarakat ini adalah model pendampingan untuk meningkatkan profesionalisme guru dalam mempersiapkan kegiatan belajar mengajar, terutama dalam menyusun perangkat pembelajaran, di mana diperlukan pemahaman dasar teori serta pengaplikasiannya. Jumlah peserta yang menghadiri kegiatan ini sebanyak 33 orang guru matematika dari kabupaten Musi Rawas. Secara keseluruhan, pelaksanaan kegiatan pengabdian ini berjalan lancar tanpa ada hambatan yang berarti, hanya saja terdapat beberapa peserta yang terkeluar dari Zoom meeting saat pelaksanaan kegiatan berlangsung secara synchronous dikarenakan gangguan signal. Hasil analisis angket respon kepuasan mendapatkan hasil yang positif